Islamic Worldview on Money and a Study of Digital Currencies from Islamic Law Perspective (Eurasian Journal of Religious Studies, 2023)
The article aims to study the digital currencies of central banks (CBDCs) in relation to the parameters of Islamic jurisprudence in particular, and the study of the monetary theory of Islam in general. CBDCs are one of the most important issues of the last decade in the field of monetary policy of countries and states. It is believed that the concept of CBDC has made a significant breakthrough in its development and has become an urgent problem for financial authorities due to the growing competition in the actively developing cryptocurrency market. Due to the fact that the concept of CBDC is constantly being developed and modified, it should be noted that it is risky to make a final judgement on CBDC. The article outlines the main stages in the evolution of money and provides a table showing the similarities and differences between electronic, crypto and digital currencies. The study then examines Islam's view of money and its monetary philosophy. The article then explores the economic and legal aspects of central bank digital currencies. Finally, the proposed solutions to these problems were presented.
Keywords: Digital currency; CBDC; Islamic worldview; Islamic jurisprudence; analysis